IMPLEMENTASI KEGIATAN PRAMUKA PRASIAGA TERHADAP PENDIDIKAN KARAKTER KEMANDIRIAN ANAK USIA DINI DI SEKOLAH ISLAM - Trisusanti; Aziz Muzaki; Ichsan; Hibana (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
Character education for Early Childhood (AUD) is a crucial aspect in forming the foundation of a child's character. The Pramuka Prasiaga activities at Islamic Schools serve as an effective method for instilling independence values from an early age. This study aims to examine the implementation of Pramuka Prasiaga activities in developing the character of independence in children aged 5-6 years at an Islamic School, as well as to identify the supporting and inhibiting factors in its implementation. This research employs a qualitative descriptive approach, with data collection techniques including observation, interviews with Scout Leaders, School Principals, and Classroom Teachers, as well as documentation. The results show that through Pramuka Prasiaga activities, children demonstrated improvements in aspects of independence, such as the ability to manage learning tasks independently, perseverance, initiative, responsibility, and self-confidence. Additionally, children exhibited strong social skills, including communication, cooperation, empathy, and mutual respect. However, there are some inhibiting factors, such as schedule conflicts between Pramuka Prasiaga activities and other school activities, weather conditions limiting outdoor activities, and interpersonal conflicts among children that reduce active participation. This study provides recommendations to improve coordination and enhance the implementation of Pramuka Prasiaga activities to maximize the development of independence character in early childhood within the school environment.